Dalla Francia a Dresda. Le Bibbie portatili della Sächsische Landesbibliothek - Staats- und Universitätsbibliothek - Paolini, Adriana (Scrineum, 2021)
The Sächsische Landesbibliothek - Staats- und Universitätsbibliothek of Dresden preserves a very interesting collection of medieval and modern manuscripts, once in the most part belonging to the Electoral Library of the Saxon Dukes. The study of the ancient catalogues of the Library has revealed the presence of five portable Bibles copied in the 13th century in the North of France and acquired by the Saxon Court on the antiquarian trade during the 18th century, except for one manuscript which was donated to the Duke Johann Georg I in the 1647. In this essay each Bible has been studied and compared with the others preserved in Dresden and also with the models of the most widespread biblical manuscripts in 13th century Europe. Although these Bibles present codicological and palaeographic features similar to the typical style of the so-called Paris Bibles, each manuscript contains significant textual and codicological variants that lead us to realize the considerable diversity of material forms and reference models circulating in the 13th century. For this reason, the essay is completed not only by a detailed description of the manuscripts but also by three further addenda in which the sequence of the books, the codicological data and the iconography are compared.